# Difference between revisions of "P. 265, Equation (7.16)"

From Bill Goodwine's Wiki

Jump to navigationJump to searchLine 6: | Line 6: | ||

<math>= \lambda^4 - k_4 \lambda^3 + \left( 3 - k_3 \right) \lambda^2 - \left(2 k_4 + k_2 \right) \lambda + \left(1 - k_1 - 2 k_3 \right) = 0.</math> | <math>= \lambda^4 - k_4 \lambda^3 + \left( 3 - k_3 \right) \lambda^2 - \left(2 k_4 + k_2 \right) \lambda + \left(1 - k_1 - 2 k_3 \right) = 0.</math> | ||

+ | |||

+ | [[Engineering Differential Equations: Theory and Applications, Springer 2010#Errata|Return to errata.]] |